PERAN SENSE OF HUMOR DALAM MEMPREDIKSI RESILIENSIPADA PESERTA PENDIDIKAN DOKTER SPESIALIS - Ghina Putri Adinda; Aflah Zakinov Irta (Jurnal Riset Psikologi, 2025)
This study examines the influence of sense of humor on resilience among specialist medical education participants (PPDS). PPDS programs subject participants to various educational challenges such as extensive workloads that can trigger stress and potentially affect mental health, making resilience an essential capacity to develop. This quantitative correlational research involved 95 PPDS participants selected through accidental sampling technique at Dr. M. Djamil General Hospital. Data collection instruments included the Multidimensional Sense of Humor Scale and Connor-Davidson Resilience Scale (CD-RISC). Simple linear regression analysis confirmed a significant influence of sense of humor on resilience (p=0.010; t=2.642). The determination coefficient of 0.272 indicates that sense of humor contributes 27.2% to resilience, while the regression coefficient value of 0.719 shows that each 1-unit increase in sense of humor corresponds to a 0.719 unit increase in resilience. The study concludes that sense of humor serves as a significant protective factor in enhancing resilience among PPDS participants, with a positive correlation between sense of humor levels and resilience capacity in facing pressures during the educational process.